Somatotypes of Indian national elite rowers - Prajapati, S. K.; Jayaraman, S. (Parishodh Journal, 2020)
Thepurpose of the study was to characterizeand determine theanthropometric variableand somatotypeof elite male national rowersof India. 8 male elite national rowers of India were selected as subjects and those subjects were represented for a country in various international competitions. The weight, stature, skin fold thickness, circumference, and widthmeasurements of the rowers participated in the study were measured based on the ISAK guidelines. Heath-Carter method was used to determine the somatotypesof rowers. To characterize the anthropometric variables, SPSS 20 was used. The mean values of the 8 male elite national rowers (n=8) were found as follows; Body Mass 88.31, Stretch Stature 184.27, Triceps Skinfold 13.52, Subscapular Skinfold 16.80, Biceps Skinfold 5.62, Iliac Crest Skinfold 21.01, Supraspinale Skinfold 14.31, Abdominal Skinfold 23.86, Front Thigh Skinfold 17.46, Medial Calf Skinfold 12.02, Arm Girth Relaxed 32.72, Arm Girth Flexed And Tensed 34.52, Waist Girth 87.94, Gluteal Girth 61.00, Calf Girth 38.99, Humerus Breadth (Biepicondylar) 7.19, Femur Breadth (Biepicondylar) 10.39, Endomorphy 4.11and Mesomorphy 4.75, Ectomorph 1.87. The mean somatotype of 8 male elite national rowers of India were identified as EndomorphicMesomorph body type(4.11-4.75-1.87).